PENERAPAN MODEL PEMBELAJARAN ???DISCOVERY LEARNING??? DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN AL-QUR???AN HADITS KELAS XI MA AL-ITTIFAQIAH INDRALAYA - Susi Yeni (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2023)
From the background of this research, it is necessary to carry out reforms to increase teachers' teaching creativity in managing the Al-Qur'an Hadith learning process as an effort to improve the quality of learning. This research is based on Classroom Action Research where the discussion in this research goes through stages: cycle 1 and cycle 2. This research uses a qualitative approach. To increase students' understanding in learning Al-Qur'an Hadith through the discovery learning method. This research was conducted at MA Al-Ittifaqiah Indralaya Ogan Ilir, South Sumatra, in two cycles. In the first cycle, one meeting was held, this meeting was used to convey learning material to students in accordance with the RPP, learning methods and learning media specified, then conduct an evaluation. From the results of observations, it shows that there has been an increase in student understanding, in the first cycle the student evaluation results were only an average of 70.45, then in the second cycle it increased to an average of 85. The results of the research prove that the discovery learning model has a significant influence on learning outcomes. students in Al-Qur'an Hadith subjects Keywords : Discovery Learning, learning result, Al-Qur'an Hadith